Heavy Metal Distribution and Bioaccumulation Combined With Ecological and Human Health Risk Evaluation in a Typical Urban Plateau Lake, Southwest China - Liu, Xi; Zhang, Junqian; Huang, Xiaolong; Zhang, Lu; Yang, Chao; Li, Enhua; Wang, Zhi (Frontiers in Environmental Science, 2022)
Heavy metal contamination in lakes caused by the rapid industrialization and urbanization is a serious problem. In this study, 12 heavy metals were systematically surveyed in aquatic environment and organisms of Dianchi Lake. Results showed that heavy metals pollutions in surface water exhibited a decreasing order of Ba > Fe > Zn > Mn > As >Ni > Cr > Cu > Pb > Cd > Co, equipped a consistency in spatial distribution, seriously contaminating the northern and southern parts. The average concentration of sedimentary heavy metals appeared in an order of Fe > Mn > Zn > Ba > Cu > Pb > Cr > As > Ni > Co > Cd > Ag. The main existing fraction (51.9%–75.0%) of Cu, Pb, Cr, As, Fe, Co, Ni, Ag, and Ba in sediments was residual fraction, whereas the exchangeable fraction (40.9%–62.0%) was the dominant component for Cd, Zn, and Mn. Among the selected aquatic organisms, Cu, Pb, Zn, and Ag possessed a strong bioaccumulation effect, followed by Mn, Fe, Co, and Ni. Ecological risk assessment indicated that Cu, Cr, and Zn were the dominant heavy metal contaminants in surface water; Cd presented the disastrous risk and accounted for the considerable proportion of ecological risk in sediments. Human health risk evaluation showed that the selected aquatic products of Dianchi Lake were not absolutely safe, and As was the major contributor. This study systematically revealed heavy metal distributions in aquatic environments, which was conductive to environmental safety and human health.